Pengembangan Prototipe Kontemporer Piranti Lunak Akuisisi dan Reduksi Data Terowongan Angin Kecepatan Rendah Indonesia - Ivransa Zuhdi Pane (Ultima Computing : Jurnal Sistem Komputer, 2014)
Data acquisition and reduction software plays an important role in providing accurate and reliable aerodynamics information for all stakeholders in a wind tunnel test. Step-by-step development through prototyping cycles promotes the creation of data acquisition and reduction software which is in accordance with the requirement definition. Test in virtual machine environment showed adequate performances which in turn suggests further implementation of the software prototype for the real applications. Index Terms—wind tunnel test, data acquisition and reduction, prototype, software engineering